Comparative characterization of microstrip patch antenna array with defected ground structure for biomedical application - Suganthi Santhanam; Thiruvalar Selvan Palavesam (Institute of Advanced Engineering and Science, 2022)
In this paper, microstrip dual band antenna array with defected ground structure has been proposed for low frequency wearable on-body applications. The array has been simulated with Cotton, Polyimide, Polyester and Teflon (PTFE) flexible materials which are mostly used for biomedical applications. The performance of 2x2 trapezoidal patch array with partial ground, thin slot defection at center has been studied in terms of return loss, VSWR, power handling capability, radiation pattern and surface current distribution. All substrates exhibits acceptable fractional bandwidth below -10 dB and Cotton proves its superiority than other substrates with -20 dB and -48 dB return loss with 16.12% and 7.73% bandwidth at 1.24 GHz and 1.94 GHz respectively. The proper matching of array has been proved with VSWR value below 1.3 for all substrates. The observation of input port impedance shows that, Cotton array has good impedance matching nearly to 50 Ω and PTFE array has 100 Ω poor impedance matching. The proposed four flexible array exhibit omnidirectional pattern in H plane with 1.43 dBi gain and bidirectional pattern in E plane with 1.4 dBi gain which are support for ideal fitness of proposed flexible material array for medical applications.